Impact of Tibetan Plateau vertical heating on the Asian summer monsoon on the interdecadal scale. (21st October 2022) - Yu, Liwei; Si, Dong; Shen, Xinyong; Lang, Xianmei; Zhang, Ran; Li, Qingquan
Abstract: This study investigated the impacts of Tibetan Plateau vertical heating (TPVH) on the Asian summer monsoon (ASM) on the interdecadal scale since the beginning of the 20th century. The ASM, corresponding to TPVH, generally enhances on the interdecadal scale. In the upper troposphere, the upper‐level westerly and easterly jet streams shift northwards in Asia, with two meridional "southern low and northern high" wave‐like patterns dominating in East Asia and India, respectively. In the lower troposphere, the summer monsoonal airflow and convergence zone migrate northwards in Asia, and two meridional "southern high and northern low" patterns appear in East Asia and India, respectively. Thus, TPVH can strengthen the baroclinicity over northern East Asia and northern India, but weaken it over southern East Asia and southern India. Moreover, two anomalous meridional circulation cells are identified in East Asia and India, with ascending branches in their northern parts and descending branches in their southern parts. Eventually, the ASM strengthens, leading to a southern dry and northern wet pattern in East Asia and India. Abstract : The East Asian summer monsoon (ASM) and Indian summer monsoon, corresponding to the Tibetan Plateau vertical heating (TPVH), generally exhibit similar variation on the interdecadal scale. The TPVH can strengthen the baroclinicity over northern East Asia and northern India, but weaken it over southern East Asia and southern India. The ASM strengthens, corresponding to the TPVH, leading to a southern dry and northern wet pattern in East Asia and India.